Effects of Zaprinast and Rolipram on Olfactory and Visual Memory in the Social Transmission of Food Preference and Novel Object Recognition Tests in Mice - Furuzan Akar; Oguz Mutlu; Ipek K. Celikyurt; Emine Bektas; Mehmet H. Tanyeri; Guner Ulak; Pelin Tanyeri; Faruk Erden (AboutScience Srl, 2014)
The role of phosphodiesterase (PDE) inhibitors in central nervous system has been investigated and shown to stimulate neuronal functions and increase neurogenesis in Alzheimer patients. The aim of this study is to investigate effect of PDE5 inhibitor zaprinast and PDE4 inhibitor rolipram on visual memory in novel object recognition (NOR) test, on olfactory memory in social transmission of food preference (STFP) test, and also on locomotion and anxiety in open field test in naive mice. Male Balb-c mice were treated intraperitoneally (i.p.) with zaprinast (3 and 10 mg/kg), rolipram (0.05 and 0.1 mg/kg), or physiological saline. Zaprinast (10 mg/kg) significantly increased cued/non-cued food eaten compared to control group, while rolipram had a partial effect on retention trial of STFP test. Zaprinast (10 mg/kg) and rolipram (0.05 and 0.1 mg/kg) significantly increased ratio index (RI) compared to control group in retention trial of NOR test. There was no significant effect of zaprinast and rolipram on total distance moved, speed, and center zone duration in open field test. Results of this study revealed that both zaprinast and rolipram enhanced visual memory in NOR test, however zaprinast exerted a significant memory-enhancing effect compared to rolipram in STFP test in mice.